Urban Critical Infrastructure’s Governance Framework for Climate Resilient Cities - Lomba-Fernández, Cinta (European Journal of Sustainable Development, 2020)
Climate change affects cities worldwide conditioning their sustainable development. Cities will concentrate around 70% of the world population by 2050 accounting for 75% of the world’s resources consumption. For that reason, cities must act against climate change adopting resilience strategies. Resilience strategies recognize the importance of the reliability and functioning of urban critical infrastructures as they provide essential services for the citizens and they are crucial for the resolution and recovery of the crises. However, the integration of critical infrastructures in the city climate resilience strategies is challenging because critical infrastructures are complex systems, strongly interconnected one to each other and generally, they belong or are operated by private companies. This research proposes a governance framework for better integration of the management of urban critical infrastructures into the city climate resilience strategy. The framework has been developed from academic literature and has been enriched with insights from workshops and interviews with experts and practitioners. As a result, the framework tackles four aspects of governance: (1) modes of governance; (2) stakeholders’ roles; (3) processes and (4) instruments. These aspects will help to improve the vertical integration, cross-sectorial coordination, innovation and knowledge, and cooperation needed for improving city resilience. Keywords: City Resilience; Urban Critical Infrastructures; Governance Framework; Climate Change Adaptation